Prognostic value of neutrophil-to-lymphocyte ratio dynamics in patients with septic acute kidney injury: a cohort study - Wei Wei; Caihong Liu; Guojiao Song; Letian Yang; Jian Li; Bo Wang; Ting Yin; Yingying Yang; Liang Ma; Ling Zhang; Ping Fu; Yuliang Zhao (Renal Failure)
Background Neutrophil-to-lymphocyte ratio (NLR) has been suggested to be a prognostic marker for various diseases, but whether NLR dynamics (ΔNLR) is related to mortality and disease severity in patients with septic acute kidney injury (AKI) has not been determined.Methods Between August 2013 and August 2021, septic AKI patients at our center were retrospectively enrolled. ΔNLR was defined as the difference between the NLR at septic AKI diagnosis and at hospital admission. The relationship between the ΔNLR and mortality was evaluated by Kaplan–Meier curves, Cox proportional hazards, and cubic spline analyses. The prediction values were compared by area under the receiver-operating characteristic curve (AUROC), net reclassification improvement (NRI), and integrated discrimination improvement (IDI) analyses.Results Of the 413 participants, the mean age was 63 ± 17 years, and 134 were female (32.4%). According to the median value, patients in the high-ΔNLR group had significantly greater 90-d mortality (74.4% vs. 46.6%, p < 0.001). After adjustment for potential confounders, high ΔNLR remained an independent predictor of 90-d mortality (HR = 2.80; 95% CI = 1.74–4.49, p < 0.001). Furthermore, ΔNLR had the highest AUROC for 90-d mortality (0.685) among the various biomarkers and exhibited an improved NRI (0.314) and IDI (0.027) when incorporated with PCT and CRP. For secondary outcomes, patients with high ΔNLR had increased risk of 30-d mortality (p = 0.004), need for renal replacement therapy (p = 0.011), and developing stage-3 AKI (p = 0.040) according to the adjusted models.Conclusions High ΔNLR is independently associated with increased risk of patient mortality and adverse outcomes. ΔNLR might be utilized to facilitate risk stratification and optimize septic AKI management.